The isotope hydrology of the Muskoka River Watershed, Ontario, Canada. Issue 4 (25th December 2019) - James, April L.; Dusome, Emily; Field, Tim; Yao, Huaxia; McConnell, Chris; Beaton, Andy; Tafvizi, Arghavan
Abstract: Stable isotope tracers of δ 18 O and δ 2 H are increasingly being applied in the study of water cycling in regional‐scale watersheds in which human activities, like river regulation, are important influences. In 2015, δ 18 O and δ 2 H were integrated into a water quality survey in the Muskoka River Watershed with the aim to provide new regional‐scale characterization of isotope hydrology in the 5, 100‐km 2 watershed located on the Canadian Shield in central Ontario, Canada. The forest dominated region includes 78, 000 ha of lakes, 42 water control structures, and 11 generating stations, categorized as "run of river." Within the watershed, stable isotope tracers have long been integrated into hydrologic process studies of both headwater catchments and lakes. Here, monthly surveys of δ 18 O and δ 2 H in river flow were conducted in the watershed between April 2015 and November 2016 (173 surface water samples from 10 river stations). Temporal patterns of stable isotopes in river water reflect seasonal influences of snowmelt and summer‐time evaporative fractionation. Spatial patterns, including differences observed during extreme flood levels experienced in the spring of 2016, reflect variation in source contributions to river flow (e.g., snowmelt or groundwater versus evaporatively enriched lake storage), suggesting more local influences (e.g., glacial outwash deposits). Evidence of combined influences of source mixing and evaporative fractionation could, in future, support application of tracer‐enabled hydrological modelling, estimation of mean transit times and, as such, contribute to studies of water quality and water resources in the region. Abstract : In 2015–2016, stable isotope tracers of δ 18 O and δ 2 H were integrated into a water quality survey of the Muskoka River Watershed ON CA, providing characterization of stable isotopes across the 5, 100‐km 2 regional‐scale watershed for the first time. Distinct labelling of source waters allows assessment of the influence of lake/wetland storage on streamflow as distinct from other sources (e.g., groundwater and snowmelt), including during extreme flows in the spring of 2016. Results also suggest local importance of groundwater connection from glacial deposits.